Transformasi Dakwah Komunitas Muslimah: Komunikasi Dialogis-Adaptif pada Masyarakat Multikultural - Siti Zaida Hanum; Baidawi (Pawarta: Journal of Communication and Da'wah, 2025)
The transformation of da'wah communication in multicultural urban environments reflects the dynamic interaction between religious messages in diverse social contexts. This study investigates how da'wah communication practices evolve within urban Muslimah communities in Indonesia, with a focusing on their adaptation to multicultural challenges and opportunities. This research is a library study that aims to understand the transformation of Islamic Preaching Communication in a multicultural society. The findings show a significant shift from conventional and one-way da'wah delivery to an interactive, dialogical, and contextually adaptive communication model. This transformation is driven by the challenges of Multicultural Da'wah among Muslim Women's Communities, Da'wah Transformation in the Muslim Women's Community Environment, and the Role of Digital Media in Comprehensively Reaching the Audience. This study concludes that the transformation of da'wah communication and media is not only a necessity, but also a necessity in facing the complexity of a modern, multicultural society. The urban Muslim community in Indonesia proves that more inclusive, dialogical, and adaptive da'wah can be a unifying bridge amidst differences.